TANGGUNG JAWAB MASKAPAI PENERBANGAN TERHADAP JAM TERBANG PILOT YANG MELEBIHI BATAS JAM TERBANG DITINJAU BERDASARKAN PERATURAN MENTERI PERHUBUNGAN NOMOR 28 TAHUN 2013 TENTANG PERATURAN KESELAMATAN PENERBANGAN SIPIL (STUDI KASUS DI PT LION MENTARI AIRLINES) - Setiadi, Muhammad Yogi; Bachtiar, Maryati; Fitriani, Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Flight characteristics and have a distinct advantage that is more technologically advanced, able to move quickly, solid capital, reliable management, as well as the need of security and safety that need dikembangankan potential and the role that effective and efficient in order to be able to create the distribution pattern of the national good and dynamic , Inside Flights are two subjects that are directly involved in the process, namely airlines and airline passengers. Liabilities airline was carrying passengers and / or goods safely, intact and safely to their destination, provide good service, compensate passengers with a schedule that has been set and others, while liabilities passengers are paying transportation costs which amount has been determined, keep the goods under its control and report any types of goods carried. But the airline using a practical way in order to earn big profits without undermining the security and safety of passengers by employing a fleet and pilots to fly longer hours specified in the Regulation of the Minister of Transportation No. 28 Year 2013 About the Civil Aviation Safety Regulations (CASR).The purpose of writing this essay, namely; First, to determine the settings Pilot Flying Hours PT Lion Mentari Airlines. Second, to determine responsibilities and sanctions received any airline pilots assigned to fly longer hours.This type of research is a sociological study, because writer research on the effectiveness of the laws in force. This research was conducted at Sultan Syarif Kasim II Pekanbaru, while the sample population is a whole party related to the issues examined in this study, the data source used, primary data, secondary data and data tertiary data collection techniques in this study with interviews, questionnaires and literature study.From the research problem there are two main things that can be inferred. First, Many cases of aircraft accidents caused by human negligence caused Airlines to earn big profits without regard to the security and safety of the flight. Second, to prevent air accidents, the supervision of the pilot flying hours over the note. Advice writer, First, it should improve its supervision of flight times, flight hours, air kelaikkan of the entire airline. Second, the airline must report not only flying schedule, the number of passengers and cargo but also obliged to report who the pilot in command to serve the flight schedule. Keywords : Airline - Flight - Pilot - Flying Hours